Analysis of the emergency water supply of the city in the Subcarpathian province - Galant, Damian; Rak, Janusz (Instal, 2024)
The analysis of crisis water supply concerns the city in the Subcarpathian province. It is supplied from two surface water intakes and there are 5 pure water supply reservoirs in the water supply network. The study balances the demand for water for human physiological purposes, the minimum amount of water, the necessary amount of water and the required amount of water in an emergency situation. For 7 settlements of the city, the needed number of 1.5 dm3 bottles, the number of 5 dm3 containers and the needed number of barrel trucks were calculated. Diversification of water supply sources and allocation of water in network water supply reservoirs were evaluated using the Shannon-Weaver index. The results presented in the paper form the basis for the implementation of Water Security Plans for the this city.